Analiza ekonomiczna i srodowiskowa dzialan z zakresu efektywnosci energetycznej w rolnictwie (Economic and environmental analysis of activities in the field of energy efficiency in agriculture) - Meyer-Aurich, A (2014)
This text is the result of the collaboration of the partners of the AGREE work-package “Economic and environmental analysis”, which is based on case study analyses of the partners in seven countries of the EU. The case studies show economic and environmental trade-offs in the different regions in the EU, for which each partner is responsible. Nevertheless prior to the reporting of the case studies an intensive discussion on a common methodological approach has been accomplished and applied to the case studies. The case studies show a wide range of different perspectives of energy efficiency in agriculture, but they are all based on the common methodology presented in Chapter 3. In Chapter 4, the case studies are presented, with authors indicated at the beginning of each section. Each section of Chapter 4 ends with a synthesis analysis of the results from the different case studies. Chapter 5 summarizes and concludes the report by highlighting the major findings of the analyses. The report builds upon the “State of the Art in Energy Efficiency in Europe” published separately by the AGREE consortium (Gołaszewski et al. 2012), which shows the status quo of energy use and possible energy efficiency measures in agriculture across different production systems and regions in Europe. This report presents an economic and environmental analysis based on in-depth case studies which show the potential for, and constraints on, energy efficiency measures in agriculture with respect to the specific environments in Europe.